2018
DOI: 10.21608/ajas.2018.26930
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Faba bean with Some Crops and Its Impact on the Production, Phyllosphere and Rhizosphere Microorganisms Under Modern Irrigation Systems

Abstract: Two field experiments were carried out at Arab El-Awammer Research Station, Assiut Governorate, Agricultural Research Centre, during 2016-2017 and 2017-2018 seasons. The present study assessed the effect of intercropping faba bean with some crops on the production, phyllosphere and rhizosphere microorganisms under modern irrigation systems. Two separates experiments were done and each experiment was subjected to one of studied irrigation systems (sprinkler and drip irrigations). Each experiment contained seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
6
1
0
Order By: Relevance
“…They attributed this result to the increased above and below ground competition in the intercropping system, where late transplanting times in onion on 15 th January and the dense faba bean sowing would lead to severe competition among plants for water, light and nutrients, resulting in the production of less vigorous plants. These findings were consistent with those obtained by Singh and Singh (2002), Aboukhadra et al (2013), Abou-Keriasha et al (2013 and Mahmoud, et al (2018).…”
Section: ) Faba Bean Plants:-supporting
confidence: 93%
See 2 more Smart Citations
“…They attributed this result to the increased above and below ground competition in the intercropping system, where late transplanting times in onion on 15 th January and the dense faba bean sowing would lead to severe competition among plants for water, light and nutrients, resulting in the production of less vigorous plants. These findings were consistent with those obtained by Singh and Singh (2002), Aboukhadra et al (2013), Abou-Keriasha et al (2013 and Mahmoud, et al (2018).…”
Section: ) Faba Bean Plants:-supporting
confidence: 93%
“…These findings are in line with previous researchers Abou- Keriasha et al (2012);Hamd Alla et al (2014), Sheha (2016), Shehata Manal (2017 and Mahmoud et al (2018), who claimed that the economic benefit of intercropping was reflected in the increased MAI values. (7) Economic evaluations:…”
Section: ) Faba Bean Plants:-supporting
confidence: 92%
See 1 more Smart Citation
“…It was reported that, the most prevalent genus isolated from all phyllosphere samples of faba bean as Aspergillus, which accounted for 50.87% of the total number of phyllosphere fungal species. Rhizopus stolonifer came in second, contributing 19.56% of the total number of phyllosphere fungi [34]. The genus Penicillium has been described from the phyllosphere of other plants, including wheat [35], which is consistent with our results.…”
Section: Isolation Of Phyllosphere Fungisupporting
confidence: 91%
“…This sole-cropped faba bean might have had no interspecific competition and also had enough sunlight to photosynthesize and the food translocates sufficiently to the sink and the endosperms of the grain become well developed that may have contributed increments in grain mass. Mahmoud et al [ 48 ] also indicated that HSW of faba bean was higher (58.52 g) in sole cropping and significantly decreased when intercropped with onion (57.44 g), garlic (57.18 g) and fennel (56.03 g).…”
Section: Resultsmentioning
confidence: 99%